Preliminary analysis of linear and angular kinetic parameters of the gait of individuals with cerebral palsy (Research, Society and Development, 2022)
Normal gait patterns allow the identification of the normal movement pattern, such as the gait of people with cerebral palsy. Paralympic classification systems aim to include the participation in sports of people with cerebral palsy, minimizing the impact of the injury on the result of the competition. In this context, this study aims to investigate, functionally, the linear and angular kinetic parameters of gait in individuals with cerebral palsy. 15 participants with cerebral palsy were classified into three groups according to the classification of the International Paralympic Committee: 1) T35- diplegic; 2) T36- athetoid ataxic; 3) T37- hemiplegic. For data acquisition, we used a motion capture system in 3 dimensions. The results showed significant differences between the three groups in some linear and angular gait variables, corroborating the qualitative classification process already used by the International Paralympics Committee. In addition, we identified the existence of people with different levels of cerebral palsy within a single functional class of International Paralympics Committee.  We found significant differences in some linear and angular gait variables among the classes T35, T36 e T37, which suggest "subgroups" inside each category, and this would prevent a athlete from competing on equal terms with the other competitors.